Adolescent health promotion based on community-centered arts education - Anny Giselly Milhome da Costa Farre; Patrícia Neyva da Costa Pinheiro; Neiva Francenely Cunha Vieira; Fabiane do Amaral Gubert; Maria Dalva dos Santos Alves; Estela Maria Leite Meirelles Monteiro
ABSTRACT Objective: To evaluate the contribution of arts education to health promotion of adolescents in situations of urban social vulnerability. Method: Participatory evaluative research, with a qualitative approach, using as a reference the theoretical constructs of Paulo Freire's Conscientization and the Empowerment Evaluation as a method of collecting with adolescents and teachers of an arts education program in the field of the Family Health Strategy. Results: Participants constructed a collective mission that represented the concept of adolescent health promotion. Arts education activities were prioritized and ranked with a mission focus, and over a three-month period, the program implemented health goals through art. In the reevaluation, the group presented a broad look at the implementation of activities and self-determination for change. Final considerations: Arts education is a potential space for nurses to act in the conscientization and empowerment of adolescent health in Primary Health Care.